2007
DOI: 10.1073/pnas.0605064103
|View full text |Cite
|
Sign up to set email alerts
|

Solar influence on climate during the past millennium: Results from transient simulations with the NCAR Climate System Model

Abstract: The potential role of solar variations in modulating recent climate has been debated for many decades and recent papers suggest that solar forcing may be less than previously believed. Because solar variability before the satellite period must be scaled from proxy data, large uncertainty exists about phase and magnitude of the forcing. We used a coupled climate system model to determine whether proxy-based irradiance series are capable U nderstanding and quantifying natural climate variability on decadal to c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
282
2
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 352 publications
(300 citation statements)
references
References 54 publications
(71 reference statements)
11
282
2
5
Order By: Relevance
“…Its variation is consistent with that of the summer APO index reconstructed from the tree-ring width in Sha County, Fujian Province [36] [37] was used to simulate the longer-term change of the summer APO index over past millennium [38] and the simulated APO was compared with the reconstruction of Zhou et al [30]. The external forcing data used in the model are taken from the reconstructions of Ammann et al [39] and include the effects of solar activity and volcanic eruption on effective solar radiation and greenhouse gases. Moreover, sulfate aerosol changes during 1870-1999 were also taken into account.…”
Section: Datamentioning
confidence: 99%
“…Its variation is consistent with that of the summer APO index reconstructed from the tree-ring width in Sha County, Fujian Province [36] [37] was used to simulate the longer-term change of the summer APO index over past millennium [38] and the simulated APO was compared with the reconstruction of Zhou et al [30]. The external forcing data used in the model are taken from the reconstructions of Ammann et al [39] and include the effects of solar activity and volcanic eruption on effective solar radiation and greenhouse gases. Moreover, sulfate aerosol changes during 1870-1999 were also taken into account.…”
Section: Datamentioning
confidence: 99%
“…Medieval climate was also characterized by hydrometeorological variability across North America (Cook et al, 2007) and Eurasia (Treydte et al, 2006). Solar and volcanic activity (Crowley, 2000;Ammann et al, 2007), solar-oceanic feedbacks (Bond et al, 2001), ocean circulation (Broecker, 2001), Pacific Ocean-atmospheric processes (Cook et al, 2007), and land-use changes Ruddiman, 2007) have all been proposed as factors influencing MCA-LIA climate.…”
Section: Introductionmentioning
confidence: 99%
“…[3] The record of atmospheric CO 2 concentration extracted from the ice cores drilled at Law Dome (East Antarctica) covering the last 2000 years MacFarling Meure et al, 2006] has been extensively used in modeling studies to constrain the global C cycle of the past [Joos and Bruno, 1998;Trudinger et al, 1999Trudinger et al, , 2005 and its interactions with the climate system [Ammann et al, 2007;Cox and Jones, 2008;Frank et al, 2010]. Models of the global C cycle that include the stable isotopes of C [Joos et al, 1999;Trudinger et al, 2002b;Gerber et al, 2003;Köhler et al, 2006] have found an additional constraint in the companion record of ı 13 C from the same site in Antarctica [Francey et al, 1999, hereinafter F99].…”
Section: Introductionmentioning
confidence: 99%